Progression of a rare multiple cystic lung disease - Gera, Kamal; Lall, Ajay; Kulshrestha, Ritu; Singh, Kanika; Chhabra, Nandini (Lung India, 2017)
Differential diagnosis of multiple cystic lung disease:[1] LymphangioleiomyomatosisPulmonary Langerhans cell histiocytosis (PLCH)Folliculin gene-associated syndrome: Extrapulmonary symptoms can occur in 10%-15% of these patients with skin rashes, lymphadenopathy, bone pains, or diabetes insipidus (hypothalamic involvement). Clinical-radiologic-pathologic correlation of smoking-related diffuse parenchymal lung disease.